PENGARUH APLIKASI BIOCHAR KULIT KAKAO TERHADAP KEMANTAPAN AGREGAT DAN PRODUKSI TANAMAN JAGUNG PADA ULTISOL LAMPUNG TIMUR - Farahmitha Shalsabila; Sugeng Prijono; Zaenal Kusuma (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2017)
Ultisols are characterized by less aggregate stability, high clay, solid, organic material, and low pH. These can be managed by using calcification, augmentation of organic material and fertilization. One of soil amendments than can be used to improve properties of Ultisol is biochar. Â The objective of this study was to elucidate the effects of cocoa's shell biochar application on soil aggregate stability and growth and yield of maize at an Ultisol. Treatments tested in this study were D0 (no biochar application), D5 (application of 5 t biochar ha-1), D10 (application of 10 t biochar ha-1), D15 (application of 15 t biochar ha-1), D25 (application of 25 t t biochar ha-1), dan D40 (application of 40 t biochar ha-1). The results showed that in one growing season giving some doses cocoa's shell biochar had not been able to affect soil aggregate stability. The highest aggregate stability was found at treatment of 15 t ha-1 of cocoaâ€™s shell biochar with an index of 130.12. The increased levels of soil organic C was followed by the increase in aggregate stability index. The highest organic C was found at D40 treatment with 4,09%. While the highest retention of water was found at the D10 with 32,96%. The increased aggregate stability index was not followed by the ability of soil to retain water. The addition of cocoa's shell biochar could increase soil organic C but not in line with the ability to retain water. If cocoa's shell biochar was given at the hig dose then it can give high maize yield.